On thin ice – The Arctic commodity extraction frontier and environmental conflicts - Hanaček, Ksenija; Kröger, Markus; Scheidel, Arnim; Rojas, Facundo; Martínez-Alier, Joan (Ecological Economics, 2021)
This article contributes to the discussion on socio-environmental conflicts and extractive projects in the Arctic region. Fifty-three socio-environmental conflicts are analysed, using data from the Global Atlas of Environmental Justice. Based on descriptive statistics, regression and network analysis, the paper reveals that socioenvironmental conflicts predominantly overlap with Indigenous peoples' territories, from which a transversal opposition takes place, including Indigenous, non-Indigenous and international actors alike. The main commodities involved in these conflicts are related to fossil fuels, metals, and transport infrastructure. Associated large-scale extractive activities are bringing negative socio-environmental impacts at the expense of Indigenous groups, fishermen, and pastoralists, with loss of traditional knowledge and practices being significantly higher in Indigenous territories of high bio-cultural values associated to the environment. Our findings suggest that repression against activists is significantly more likely to occur in absence of preventive mobilization, and in Arctic countries with low rule of law. The chances to achieve the cancellation of a conflictive extractive project are significantly higher if dependency on natural resource rents in a country is low. Peer reviewed